DERIVATIONAL MODELS OF SOCIO-POLITICAL TERMINOLOGY IN URDU - Shamsutdinova Shahnoza; Abdurahmanova M.H (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, words related to Urdu socio-political vocabulary are separated from journalistic texts and analyzed according to their derivational features.